2017
DOI: 10.1177/0091217417720894
|View full text |Cite
|
Sign up to set email alerts
|

The association of generalized anxiety disorder and Somatic Symptoms with frequent attendance to health care services

Abstract: Objective Generalized anxiety disorder is associated with higher rate of physical comorbities, unexplained symptoms, and health care utilization. However, the role of somatic symptoms in determining health care utilization is unclear. The present study aims to assess the association of frequent attendance of health care services between generalized anxiety disorder symptoms and somatic symptoms. Method This study was conducted cross-sectionally using the material of the 46-year follow-up survey of the Northern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…33 In addition, Simoen et al 33 reported higher levels of anxiety symptoms among consecutive TMD pain patients compared to the general population in Belgium. In Finland, the corresponding prevalence in high health care utilisers in the Northern Finland Birth Cohort 1966 was shown to be lower, 46 and GAD-7 was shown to be valid and useful tool for screening for anxiety disorders in primary health care.…”
Section: Discussionmentioning
confidence: 99%
“…33 In addition, Simoen et al 33 reported higher levels of anxiety symptoms among consecutive TMD pain patients compared to the general population in Belgium. In Finland, the corresponding prevalence in high health care utilisers in the Northern Finland Birth Cohort 1966 was shown to be lower, 46 and GAD-7 was shown to be valid and useful tool for screening for anxiety disorders in primary health care.…”
Section: Discussionmentioning
confidence: 99%
“… 24 A recent study showed generalized anxiety disorder and somatic symptoms associating with frequent health care use. 25 …”
Section: What Has It Found? Key Findings and Publicationsmentioning
confidence: 99%
“…2 Despite comorbidities, it is the somatic complaints in GAD that often drive patient requests for medical care. 7,8 GAD itself is an independent predictor of heart disease 9 and is linked to increased risk of chronic or severe headaches 10 and suicide. 11,12 Work with patients and family toward a diagnosis Despite the potential benefits of early identification and treatment of GAD, 13 the average elapsed time from symptom onset to initial medication treatment is 7 years.…”
Section: Gad Diagnostic Criteria and Differential Considerationsmentioning
confidence: 99%